Design, Synthesis, and in Vitro and in Vivo Anticancer Activity Studies of New (s)-naproxen Thiosemicarbazide/1,2,4-triazole Derivatives - Han, M. Ihsan; Tunc, Cansu Umran; Atalay, Pinar; Erdogan, Omer; Unal, Gokhan; Bozkurt, Mehmet; Kucukguzel, S. Guniz (Royal Soc Chemistry, 2022)
In this study, a series of novel (S)-Naproxen derivatives bearing a thiosemicarbazide/1,2,4-triazole moiety were designed, synthesized, and evaluated for anticancer activity. The structures of these compounds were characterized by spectral (H-1-C-13 NMR, FT-IR, and HR-MS analyses) methods. All of the synthesized compounds (3a-m, 4a-j) were screened for anticancer activity against human breast cancer cell line MDA-MB-231. Among them, (S)-4-(2,4-dichlorophenyl)-5-[1-(6-methoxynaphthalen-2-yl)ethyl]-4H-1,2,4-triazole-3-thione (4b) showed the most potent anticancer activity with a good selectivity (IC50= 9.89 +/- 2.4 mu M). Inhibition of anti-apoptotic protein Bcl-2 was investigated in MDA-MB-231 cells treated with compound 4b using Western Blotting. Apoptosis was also detected by AO/EB and JC-1 staining. Furthermore, activation of caspase-3 enzyme activity demonstrated apoptosis. The flow cytometric analysis results showed that compound 4b decreases the number of cells in the G2/M phase and increases the cells in the S phase in a dose-dependent manner. The anticancer activity of compound 4b was also investigated. In the Ehrlich acid tumor model, a well-validated in vivo ectopic breast cancer model, compound 4b had anticancer activity and reduced the tumor volume at both low (60 mg kg(-1)) and high (120 mg kg(-1)) doses in mice, according to our in vivo results.
BOZKURT, MEHMET/0000-0003-2965-6719; Aydin, Omer/0000-0002-9028-8786; Han, Muhammed Ihsan/0000-0001-5610-0869; Tunc, Cansu Umran/0000-0002-8555-1340; erdogan, omer/0000-0002-8327-7077
Keywords: [No Keyword Available]